Resonant Properties of Perforated Screen with Two Circiular Below-Cutoff Holes of Different Diameter in Periodic Cell - Kirilenko, A. A.; Perov, A. O.; Senkevich, S. L. (Видавничий дім «Академперіодика», 2012)
The resonant scattering of electromagnetic plane wave on a perforated screen with circular below-cutoff holes in a periodic cell is investigated. Several holes on a period are found to qualitatively change the screen frequency response. Along with the total transmission of the exciting field in a one wave frequency bandwidth, the total reflection mode is also possible. To explain the nature of such behavior, the perforated screen is considered as an open periodic resonator, and its eigenoscillations are analyzed. On the strength of symmetry principles, the general peculiarities of spectra formation for regular periodic structures are determined, the existence of real valued eigenfrequencies converging to zero frequency being particularly found. The oscillations determining the resonance behavior are found too, their space pattern studied.